Hubungan regulasi emosi dengan perilaku kekerasan dalam berpacaran pada mahasiswa - Puspita Megawati; Zainul Anwar; Alifah Nabilah Masturah (Fakultas Psikologi, 2019)
Ideally dating is sharing mutual love, attention, gentle treatment, intimacy, and romance. However, it is not uncommon to find abusive treatment from their loved ones. Emotional regulation with a poor ability to regulate emotions is associated with emotional arousal which leads to an increase in aggression behavior. The purpose of this study was to determine the relationship of emotional regulation with violent dating behavior in students. This study uses a correlational quantitative research method using a purposive sampling technique. The study was conducted on perpetrators of violence in dating with a total of 183 subjects with an age range of 18-24 years. Data collection uses the scale of DERS adaptation and scale of Violence in Dating. Data analysis method uses Pearson product moment analysis. The results showed a significant correlation between emotional regulation of dating violence (r= 0.360; r² = 0.130; p = 0,000; p <0.05).